Pengaruh Drainase Terhadap Budidaya Pertanian Di Lahan Basah - Arif Indra Jaya Gea; Juwita Sartika Halawa; Fersi Roman Lase; Iman Victor Telaumbanua; Febe Juniati Halawa; Yoel Melsaro Larosa (Jurnal Ilmu Pertanian dan Perikanan, 2025)
Drainage is one of the important factors in agricultural cultivation, especially on land with high humidity levels or prone to waterlogging. This study aims to analyze the effect of drainage systems on the success of agricultural cultivation in wetlands. The approach used is a descriptive qualitative method with direct observation techniques in the field and in-depth interviews with local farmers. The results of the study showed that the existence of a good drainage system can increase soil aeration, prevent root rot, and support optimal plant growth. Conversely, land without an adequate drainage system shows decreased productivity and the emergence of various plant disease problems.